Selection and Analysis of the Spring Force of Roller Clutches - Yu Xin; Xue Jinxue; Gao Fei; Xi Shiping; Zhang Kai (Jixie chuandong)
In the design process of overrunning clutches, the preload spring force has an important impact on the timely disengagement and engagement of roller clutches during the operation process, but the current spring design theory system is not complete. Through the force analysis of rollers, the range of the spring force is obtained. Then, the finite element software is used to analyze the pressure, response time and other contact characteristics of different spring forces in the clutch engagement and overrunning state, compared with the theoretical calculation and analysis. Finally, the numerical value from the elastic force range for corresponding tests is selected to verify and judge the rationality of the analysis by observing the wear of clutch parts. In this way, the selection process and test cycle of the clutch spring force are shortened, and the reliability of test results is improved.